Boosting City Image for Creation of a Certain City Brand - Shirvani Dastgerdi, Ahmadreza; De Luca, Giuseppe (Geographica Pannonica, 2019)
Global cities are increasingly competing together in order to showcase themselves as the best destination for tourists, investors, and talented people. During the last four decades, there has been a growing interest in City branding. It takes place within a communication system that closely connects the overall city image and identity. Community leaders are more and more recognizing that there is a direct link between the city image and its attractiveness as a place to visit, live, invest, and study. Aimed at developing the theoretical framework of city branding, this research attempts to identify and explain the relationship between the variables affecting the city image as a paradigmatic model of city branding and sustainable urban development. Therefore, 35 peer-reviewed articles are initially selected from the Directory of Open Access Journals (DOAJ), through purposive sampling. Then, the collected data is analyzed in four stages using grounded theory. The results of this study indicate that the boosting of city image is a complex process that continuously and dynamically requires a meaningful combination of planning, actions, and stakeholders at various organizational levels.
Keywords: global city; city branding; city image; sustainable urban development